COMBINED, International Group Exhibition, 2025, Old Electricity Board (Palia Ilektriki) in Paphos, curated by Vassiliki Vayenou and Stratis Pantazis, under the auspices of the Embassy of Austria in Cyprus and the support of the Municipality of Paphos, hosted by non-profit organization M.A.M.A (Making Art, Meeting Art) Contemporary - Pericleous, Vicky (My University, 2025)
The non-profit organization M.A.M.A (Making Art, Meeting Art) Contemporary is hosting the group exhibition COMBINED, which was presented with variations in Athens and then in Volkersdorf in Austria, at the Old Electricity Board (Palia Ilektriki) in Paphos, under the auspices of the Embassy of Austria in Cyprus and the support of the Municipality of Paphos. The exhibition derives its ideas and aims from the different meanings of the specific word, such as to add together, to come together, to unite in order to have an effect, while it activates every form of combinatorial reasoning, even that of a scheme. The implications of the word’s connotations are closely related, metaphorically and literally, to the worldwide political instability and crisis of the present years. In this light, the artworks of the participating artists expose the ways in which the financial and political crisis mechanisms divert our attention away from the devastating, irreversible effects of environmental destruction, as well as the operational modes of capitalism. In addition, multiculturalism, the systematic support of actions related to both visible and invisible divisions, intolerance, misinformation and the violation of human rights are examined. Curators: Vassiliki Vayenou and Stratis Pantazis Participating artists: Blanka Amezkua (Latinx/USA), Dimitris Georgakopoulos (Greece), Marco Goldenstein (Germany), Tamara Erde (Germany and France), Sula Zimmerberger (Austria), Collectif MASI (Madlen Anipsitaki & Simon Riedler, France and Greece), Elli Kontou (Cyprus and Greece), Marianna Constanti (Cyprus), Theodor Liho (Bulgaria), Claudia-Maria Luenig (German, based in Austria), Eleni Lyra (Greece), Cornelia Mittendorfer (Austria), Uwe Bressnik (Austria), Karen Ostrom (Canadian, based in the USA), Elena Panayotova (Bulgaria), Yiannis Pappas (Germany), Vicky Pericleous (Cyprus), Karin Maria Pfeifer (Austria), Andreas Savva (Cyprus and Greece), Makis Faros (Greece), Efi Fouriki (Greece), Yioula Hadjigeorgiou (Cyprus and Greece), Maria Hanl (Austria) Venue: Old Electricity Board (Palia Ilektriki), Vladimirou Herakleous 8, Paphos 8010 Opening: Saturday 18 October 2025, 18:30 Time: 17:30- 20:30 (everyday) Durarion: 18 – 25 October 2025 Contact information: M.A.M.A Contemporary 97843583/ 96582680 The Screening of the films/ documentaries will be announced on Facebook: Percephone, the red carpet, by COLLECTIF MASI Moonlight Jerusalem, by Tamara Erde
Keywords: Arts; Contemporary Art Practices; International Art Exhibitions; Cosmopolitanism; Political & Social Narratives; Combinatorial Reasoning